Crescimento e produção de cultivares de alface americana, em função de ambientes de cultivo e das estações do ano - Silva, Mônica Bartira da (2013)
This study aimed to evaluate the ambience on growth and yield characteristics of cultivars of lettuce in a greenhouse, greenhouse type, with and without screen termorefletora conducted in four seasons (spring, summer, autumn and winter) in an organic system. Four experiments were conducted at the experimental station belonging to the core experimental stations Unioeste, from Marechal Cândido Rondon, PR, in the period 2011/2012. The plants were evaluated for growth characteristics at 0, 10, 20, 30, and 40 days after transplanting and the productive characteristics at harvest. For this we used two experimental designs, one was on the evaluation to the development of the seedlings before transplanting where treatments were arranged in a randomized block design in a split-plot design with three replications, and the portion comprised of four production stations seedlings (spring, summer, autumn and winter), and subplots for lettuce cultivars (Kaiser, Raider Plus, Lucy Brown and Angelina). For the second design, corresponding assessments of plant growth treatments were arranged in a randomized block design in split-split plot design with three replications. The plots consisted of two rooms which are growing greenhouse gases with and without type screen termorefletora, subplots by cultivars of lettuce, and the split the season that culture was located. Each subsubplot comprised of 38 plants. Evaluated throughout the growing season plant height, crown projection, number of leaves, height and stem diameter, total dry matter of roots and shoots, we calculated the rate of crop growth rate, relative growth, net assimilation rate, leaf area ratio, specific leaf area, leaf mass ratio, and the date of collection were also evaluated the number of leaves, diameter and height of the skirt of leaves, fresh weight of shoot, productivity, commercial fresh mass, diameter, height and number of leaves commercial, compact head, incidence of "tip burn". To characterize the growth environment are derived from temperature and relative humidity, evaporation from minitanques and soil temperature. Genotype environment interaction was observed in all evaluations. The best seasons for production of lettuce in the spring and fall, and to cultivate Angelina only recommended for spring. The environment screen termorefletora decreased air temperature at the hottest times of the day, the seasons of spring, summer and fall. The final yield of lettuce was not affected by the use of the screen termorefletora